Resolution of Optic Disc Pit Maculopathy Following Posterior Vitreous Detachment. (September 2022) - Mannaa, Ali H.; Issa, Reda A.; Bryan, J. Shepard
Purpose: This work presents a case of significant improvement of optic pit disc maculopathy following an acute posterior vitreous detachment (PVD) and discusses the possible mechanisms of this phenomenon. Methods: A case report and review of the literature are presented. Results: A 56-year-old man presenting with progressive visual decline in his left eye was found to have an optic disc pit with optical coherence tomography (OCT) evidence of severe intraretinal edema and maculoschisis. His visual acuity and macular anatomy on OCT improved dramatically in the months following a PVD. Conclusions: This report presents an interesting case of spontaneous improvement of optic disc pit–related maculopathy following PVD. We discuss the cause of the retinal fluid accumulation in optic disc pit maculopathy and consider that the OCT findings in our case lend credence to the theory that this fluid originates from the vitreous humor.